Teknos (M) Sdn Bhd / Muhammad Naufal Faris - Faris, Muhammad Naufal (Faculty Of Chemical Engineering, 2022)
This industrial training report of Muhammad Naufal bin Faris to undergo an industrial training for duration of 6 months which consist of 24 weeks before completing the Diploma courses. Starting industrial training on 21st February 2022 until August 4th 2022 at Teknos (M) Sdn Bhd which guided by Mr Jacky Chan Won Hee. The purpose of this program is to fulfill the course in order to complete the Diploma as well as graduate from the university. The training refers to work experience that is relevant to professional development prior to graduate. In first chapter this report is defining the term of industrial training and description on industrial training objectives. This part explains the details of objectives of industrial training report and industrial report. In second chapter of report is overview of the company and departments. The duties that were assigned to me is is about documentation about process in the factory, also the process of technical skill. Secondly, my duties during my internship period is quality control check where check the product according to the specs. This training gives me a lot of experience on working in real life situation. I also learn on how to solve a problem in a certain situation. This training is good opportunity for students to learn about real-life working situation.